Hydrogen-rich water supplementation promotes muscle recovery after two strenuous training sessions performed on the same day in elite fin swimmers: randomized, double-blind, placebo-controlled, crossover trial - Sládečková, Barbora; Botek, Michal; Krejčí, Jakub; Valenta, Michal; McKune, Andrew; Neuls, Filip; Klimešová, Iva (Frontiers in Physiology, 2024)
Purpose: Molecular hydrogen has been shown to possess antioxidant, anti-inflammatory, ergogenic, and recovery-enhancing effects. This study aimed to assess the effect of molecular hydrogen administration on muscle performance, damage, and perception of soreness up to 24 h of recovery after two strenuous training sessions performed on the same day in elite fin swimmers. Methods: Eight females (mean ± SD; age 21.5 ± 5.0 years, maximal oxygen consumption 45.0 ± 2.5 ml.kg-1.min-1) and four males (age 18.9 ± 1.3 years, maximal oxygen consumption 52.2 ± 1.7 ml.kg-1.min-1) performed 12 × 50 m sprints in the morning session and a 400 m competitive performance in the afternoon session. Participants consumed hydrogen-rich water (HRW) or placebo three days before the sessions (1260 ml/day) and 2080 ml on the experimental day. Muscle performance (countermovement jump), muscle damage (creatine kinase), and muscle soreness (100 mm visual analogue scale) were measured during the experimental day and at 12 and 24 h after the afternoon session. Results: HRW compared to placebo reduced blood activity of creatine kinase (156 ± 63 vs. 190 ± 64 U.L-1, p = 0.043), muscle soreness perception (34 ± 12 vs. 42 ± 12 mm, p = 0.045), and improved countermovement jump height (30.7 ± 5.5 cm vs. 29.8 ± 5.8 cm, p = 0.014) at 12 h after the afternoon session. Conclusion: Four days of HRW supplementation is a promising hydration strategy for promoting muscle recovery after two strenuous training sessions performed on the same day in elite fin swimmers.